Antibacterial compounds from Salvia adenophora Fernald (Lamiaceae). (February 2015) - Bisio, Angela; Schito, Anna Maria; Ebrahimi, Samad Nejad; Hamburger, Matthias; Mele, Giacomo; Piatti, Gabriella; Romussi, Giovanni; Dal Piaz, Fabrizio; De Tommasi, Nunziatina
Graphical abstract: From the aerial parts of Salvia adenophora Fernald four derivatives of 12-oxo-phytodienoic acid (1 –4 ) together with five clerodane diterpenoids (5, 6, 8 –10 ), and one known diterpene (7 ) have been isolated. Compounds1 –6 and8 –10 are described for the first time. Three oxylipins (2 –4 ) displayed a promising inhibition on Gram-positive multidrug-resistant clinical strains including Staphylococcus aureus, Streptococcus agalactiae and, particularly, Staphylococcus epidermidis, while two clerodane diterpenoids (9, 10 ) revealed a specific and strain-dependent activity against S. epidermidis . Highlights: Isolation of four prostaglandine-like compounds and six clerodane diterpenoids. Elucidation of structures and determination of absolute configurations. Evaluation of the antimicrobial activity of the isolated compounds. Abstract: From the aerial parts of Salvia adenophora Fernald four derivatives of 12-oxo-phytodienoic acid (1 –4 ) together with five clerodane diterpenoids (5, 6, 8 –10 ), and one known diterpene (7 ) have been isolated. Compounds1 –6 and8 –10 are described for the first time. The structures were established by extensive 1D, 2D NMR and HRESI-TOFMS spectroscopic methods. Finally, the absolute configuration has been established by comparing of experimental and quantum chemical calculation of ECD spectra. Despite a total lack of antimicrobial activity of the plant extract, hinting to the existence of antagonistic interactions in the crude material, three oxylipins (2 –4 ) displayed a promising inhibition on Gram-positive multidrug-resistant clinical strains including Staphylococcus aureus, Streptococcus agalactiae and, particularly, Staphylococcus epidermidis, while the compounds9 and10 revealed a specific and strain-dependent activity against S. epidermidis . Interestingly, the inhibition provided by these compounds was independent of the resistance patterns of these pathogens to classic antibiotics. No action was reported on Gram-negative strains nor on Candida albicans . These results confirm that clerodanes and, particularly, prostaglandin-like compounds can be considered as interesting antimicrobial agents deserving further study.